2018
DOI: 10.1016/j.mcn.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Species-conserved SYNGAP1 phenotypes associated with neurodevelopmental disorders

Abstract: SYNGAP1 loss-of-function variants are causally associated with intellectual disability, severe epilepsy, autism spectrum disorder and schizophrenia. While there are hundreds of genetic risk factors for neurodevelopmental disorders (NDDs), this gene is somewhat unique because of the frequency and penetrance of loss-of-function variants found in patients combined with the range of brain disorders associated with SYNGAP1 pathogenicity. These clinical findings indicate that SYNGAP1 regulates fundamental neurodevel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 95 publications
8
77
2
Order By: Relevance
“…In heterozygous Syngap1 knockout ( Syngap1 −/+ ) mice, robust changes in behavioral phenotypes have been reported by several groups (see Table S4). Syngap1 −/+ mice show increased locomotor activity , decreased anxiety‐like behavior , impaired reference spatial memory , and impaired working spatial memory . In addition, increased stereotypic behavior , decreases in motor functions in females , elevated startle response and a decrease in prepulse inhibition , reduced social novelty preference , and impaired cued fear memory have been reported by preceding studies.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…In heterozygous Syngap1 knockout ( Syngap1 −/+ ) mice, robust changes in behavioral phenotypes have been reported by several groups (see Table S4). Syngap1 −/+ mice show increased locomotor activity , decreased anxiety‐like behavior , impaired reference spatial memory , and impaired working spatial memory . In addition, increased stereotypic behavior , decreases in motor functions in females , elevated startle response and a decrease in prepulse inhibition , reduced social novelty preference , and impaired cued fear memory have been reported by preceding studies.…”
Section: Introductionsupporting
confidence: 63%
“…While many studies have shown elevated locomotor activities of Syngap1 −/+ mice in novel environments in various behavioral tests , activity in familiar environment has not yet been tested . In the present study, we observed the home cage locomotor activity of these mice and found that they have a significantly increased locomotor activity at night, which indicates that these mice show hyperlocomotor activity not only in novel, but also in familiar environments.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…This delocalization of SynGAP may help to transiently increase Ras activity in stimulated spines, thereby stabilizing LTP. Indeed, the active form of Ras (Ras‐GTP) was increased in synapses after LTP induction, and restoring normal SynGAP protein levels in SYNGAP1 heterozygous knockout mice rescued both LTP and Ras‐related signaling impairments . In addition, SynGAP has been shown to suppress spine formation and maturation.…”
Section: Dendritic Spines In Neurodevelopmental Disordersmentioning
confidence: 99%